'I – from dreams to reality': A Case Study of Developing Youngsters' Self‐Efficacy and Social Skills through an Arts Educational Project in Schools. (11th July 2017) - Ruokonen, Inkeri
Abstract: This is a case study of a one‐year arts educational project ' I – from dreams to reality' in which artists worked at school with teachers and learning at the school was planned through arts‐based, co‐operative teamwork during one extra school year of 10th grade students in Finnish basic education. The theme of the year was 'I', and so the project was designed to highlight everyone's own way of thinking and expressing art. The research task was to determine whether long‐term holistic arts pedagogy and artist co‐operation at school have any significant connection to students' self‐efficacy and social skills. Data has been collected through students' self‐evaluations before and after the school year. Altogether 40 students from 10th grade participated in this case study. Half of the pupils participated in an arts educational project called 'I – from dreams to reality' and half formed the control group. Artists worked with the test group weekly during a period of one school year (altogether nine months). Students' self‐evaluations concerning their self‐efficacy and social behaviour were collected by e‐questionnaire. The measures used were Likert‐based evaluation scores of pupils' self‐assessment of their self‐efficacy and social behaviour in everyday situations at school. According to the results, artist–teacher co‐operation and learning through the arts can be worthwhile experiences to develop students' self‐efficacy and social skills.